2015
DOI: 10.1002/jcp.24824
|View full text |Cite
|
Sign up to set email alerts
|

Flt3 Ligand Induces Monocyte Proliferation and Enhances the Function of Monocyte-Derived Dendritic Cells In Vitro

Abstract: Flt3 ligand (FL), a potent hematopoietic cytokine, plays an important role in development and activation of dendritic cells (DCs) and natural killer cells (NK). Although some post-receptor signaling events of FL have been characterized, the role of FL on Flt3 expressing human peripheral blood monocyte is unclear. In the current study, we examined the role of FL on cell survival and growth of peripheral blood monocytes and function of monocyte-derived DCs. FL promoted monocyte proliferation in a dose-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
1
17
1
Order By: Relevance
“…Flt3‐L treatment of mice as seen in our study can significantly increase the populations of DCs as well as promote DC‐mediated anti‐tumor immunity. Basic and clinical studies have already shown a role of mobilized DCs by Flt3‐L in delaying tumor growth, proliferation and induction of tumor‐specific immune responses . In our study, administration of Flt3‐L resulted in markedly increasing DCs in tumor‐bearing mice, which synergized the anti‐tumor effects of DC‐targeted gene silencing of IDO; combination treatment of man‐GNR‐siIDO and Flt3‐L achieved the highest efficiency in lung cancer mice.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Flt3‐L treatment of mice as seen in our study can significantly increase the populations of DCs as well as promote DC‐mediated anti‐tumor immunity. Basic and clinical studies have already shown a role of mobilized DCs by Flt3‐L in delaying tumor growth, proliferation and induction of tumor‐specific immune responses . In our study, administration of Flt3‐L resulted in markedly increasing DCs in tumor‐bearing mice, which synergized the anti‐tumor effects of DC‐targeted gene silencing of IDO; combination treatment of man‐GNR‐siIDO and Flt3‐L achieved the highest efficiency in lung cancer mice.…”
Section: Discussionsupporting
confidence: 58%
“…However, ex vivo generated DC vaccines possess many shortcomings such as requiring large quantities of DCs, poor migration of administered DCs into lymphoid and cancer tissue, and the technical challenges faced when manufacturing large quantities of DC vaccine in vitro . An alternative strategy is mobilizing DC in vivo using the cytokine Flt3‐L, instead of ex vivo infusion of pre‐made DC vaccines . Although DC augmentation is considered a viable cancer immunotherapy strategy in clinic, the clinical outcomes have been disappointing mainly due to the mobilized DC being rendered less effective by immunosuppressive molecules, such as IDO, especially in an immune suppressed patient .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though steady state monocyte development in mice appears FLT3L-independent [42], FLT3L might influence monocyte development into cells that resemble DCs. Indeed, addition of FLT3L to human monocytes cultured in GM-CSF and IL-4 increases the yield of DC-like cells with potent T cell stimulatory capacity [56]. Murine monocytes cultured with FLT3L alone do not become superior stimulators of a mixed lymphocyte reaction [57] but the possibility remains that FLT3L might promote monocyte differentiation into DC-like cells during inflammation in vivo, which to our knowledge has not been sufficiently addressed in FLT3L or CD135 deficient animals.…”
Section: Lineage Attribution Based On Growth Factor Requirementsmentioning
confidence: 98%
“…To address whether BEC-conditioned monocytes are related to ModDCs, we analyzed the expression of a group of genes involved in DC and ModDC development (22, 31, 32), which includes Fc ε R1 α, XCR1, CSF1R, FLT3, IRF4 , and ZBTB46 (Figures 2A–F). Monocytes were cultured with medium alone or with BEC-CM for 24 or 48 h. For comparative purposes, we also analyzed the gene expression in DCs or macrophages.…”
Section: Resultsmentioning
confidence: 99%